Expedient preparative isolation and tandem mass spectrometric characterization of C-seco triterpenoids from neem oil - Haldar, Saikat; Mulani, Fayaj A.; Aarthy, Thiagarayaselvam; Dandekar, Devdutta S.; Thulasiram, Hirekodathakallu V. (Journal of Chromatography A, 2014)
C-seco triterpenoids are widely bioactive class of natural products with high structural complexity and diversity. The preparative isolation of these molecules with high purity is greatly desirable, although restricted due to the complexity of natural extracts. In this article we have demonstrated a Medium Pressure Liquid Chromatography (MPLC) based protocol for the isolation of eight major C-seco triterpenoids of salannin skeleton from Neem (Azadirachta indica) oil. Successive application of normal phase pre-packed silica-gel columns for the fractionation followed by reverse phase in automated MPLC system expedited the process and furnished highly pure metabolites. Furthermore, eight isolated triterpenoids along with five semi-synthesized derivatives were characterized using ultra performance liquid chromatography-electrospray ionization-quadrupole/orbitrap-MS/MS spectrometry as a rapid and sensitive identification technique. The structure-fragment relationships were established on the basis of plausible mechanistic pathway for the generation of daughter ions. The MS/MS spectral information of the triterpenoids was further utilized for the identification of studied molecules in the complex extract of stem and bark tissues from Neem. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: ESI(+)-quadrupole/orbitrap-MS/MS; MPLC; Neem oil; Preparative isolation; Salannin; Triterpenoids

Way toward ``dietary pesticides'': molecular investigation of insecticidal action of caffeic acid against helicoverpa armigera - Joshi, Rakesh S.; Wagh, T. P.; Sharma, N.; Mulani, Fayaj A.; Sonavane, U.; Thulasiram, H. V.; Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Agricultural and Food Chemistry, 2014)
Bioprospecting of natural molecules is essential to overcome serious environmental issues and pesticide resistance in insects. Here we are reporting insights into insecticidal activity of a plant natural phenol. In silico and in vitro screening of multiple molecules supported by in vivo validations suggested that caffeic acid (CA) is a potent inhibitor of Helicoverpa armigera gut proteases. Protease activity and gene expression were altered in CA-fed larvae. The structure-activity relationship of CA highlighted that all the functional groups are crucial for inhibition of protease activity. Biophysical studies and molecular dynamic simulations revealed that sequential binding of multiple CA molecules induces conformational changes in the protease(s) and thus lead to a significant decline in their activity. CA treatment significantly inhibits the insect's detoxification enzymes, thus intensifying the insecticidal effect. Our findings suggest that CA can be implicated as a potent insecticidal molecule and explored for the development of effective dietary pesticides.
Keywords: Caffeic acid; Helicoverpa armigera; insecticidal activity; protease inhibitor

Gedunin and azadiradione: human pancreatic alpha-amylase inhibiting limonoids from neem (azadirachta indica) as anti-diabetic agents - Ponnusamy, Sudha; Haldar, Saikat; Mulani, Fayaj A.; Smita S. Zinjarde; Thulasiram, Hirekodathakallu; RaviKumar, Ameeta (Plos One, 2015)
Human pancreatic alpha-amylase (HPA) inhibitors offer an effective strategy to lower postprandial hyperglycemia via control of starch breakdown. Limonoids from Azadirachta indica known for their therapeutic potential were screened for pancreatic alpha-amylase inhibition, a known anti-diabetic target. Studies were carried out to reveal their mode of action so as to justify their hypoglycemic potential. Of the nine limonoids isolated/semi-synthesized from A. indica and screened for alpha-amylase inhibition, azadiradione and exhibited potential inhibition with an IC50 value of 74.17 and 68.38 mu M, respectively against HPA under in vitro conditions. Further screening on AR42J alpha-amylase secretory cell line for cytotoxicity and bioactivity revealed that azadiradione and gedunin exhibited cytotoxicity with IC50 of 11.1 and 13.4 mu M. Maximal secreted alpha-amylase inhibition of 41.8% and 53.4% was seen at 3.5 and 3.3 mu M, respectively. Michaelis-Menten kinetics suggested a mixed mode of inhibition with maltopentaose (K-i 42.2, 18.6 mu M) and starch (K-i' 75.8, 37.4 mu M) as substrate with a stiochiometry of 1: 1 for both azadiradione and gedunin, respectively. The molecular docking simulation indicated plausible p-alkyl and alkyl-alkyl interactions between the aromatic amino acids and inhibitors. Fluorescence and CD confirmed the involvement of tryptophan and tyrosine in ligand binding to HPA. Thermodynamic parameters suggested that binding is enthalpically and entropically driven with Delta G degrees of -21.25 kJ mol(-1) and -21.16 kJ mol(-1) for azadiradione and gedunin, respectively. Thus, the limonoids azadiradione and gedunin could bind and inactivate HPA (anti-diabetic target) and may prove to be lead drug candidates to reduce/control post-prandial hyperglycemia.

Triterpenoid profiling and functional characterization of the initial genes involved in isoprenoid biosynthesis in neem (Azadirachta indica) - Pandreka, Avinash; Dandekar, Devdutta S.; Haldar, Saikat; Uttara, Vairagkar; Vijayshree, Shinde G.; Mulani, Fayaj A.; Aarthy, Thiagarayaselvam; Thulasiram, Hirekodathakallu V. (BMC Plant Biology, 2015)
Background: Neem tree (Azadirachta indica) is one of the richest sources of skeletally diverse triterpenoids and they are well-known for their broad-spectrum pharmacological and insecticidal properties. However, the abundance of Neem triterpenoids varies among the tissues. Here, we delineate quantitative profiling of fifteen major triterpenoids across various tissues including developmental stages of kernel and pericarp, flower, leaf, stem and bark using UPLC-ESI (+)-HRMS based profiling. Transcriptome analysis was used to identify the initial genes involved in isoprenoid biosynthesis. Based on transcriptome analysis, two short-chain prenyltransferases and squalene synthase (AiSQS) were cloned and functionally characterized. Results: Quantitative profiling revealed differential abundance of both total and individual triterpenoid content across various tissues. RNA from tissues with high triterpenoid content (fruit, flower and leaf) were pooled to generate 79.08 million paired-end reads using Illumina GA.. platform. 41,140 transcripts were generated by d e novo assembly. Transcriptome annotation led to the identification of the putative genes involved in isoprenoid biosynthesis. Two short-chain prenyltransferases, geranyl diphosphate synthase (AiGDS) and farnesyl diphosphate synthase (AiFDS) and squalene synthase (AiSQS) were cloned and functionally characterized using transcriptome data. RT-PCR studies indicated five-fold and ten-fold higher relative expression level of AiSQS in fruits as compared to leaves and flowers, respectively. Conclusions: Triterpenoid profiling indicated that there is tissue specific variation in their abundance. The mature seed kernel and initial stages of pericarp were found to contain the highest amount of limonoids. Furthermore, a wide diversity of triterpenoids, especially C-seco triterpenoids were observed in kernel as compared to the other tissues. Pericarp, flower and leaf contained mainly ring-intact triterpenoids. The initial genes such as AiGDS, AiFDS and AiSQS involved in the isoprenoids biosynthesis have been functionally characterized. The expression levels of AiFDS and AiSQS were found to be in correlation with the total triterpenoid content in individual tissues.
Keywords: Azadirachta indica; Quantitative profiling; Transcriptome; Triterpenoids

Whole-cell mediated 11 beta-hydroxylation on the basic limonoid skeleton by cunninghamella echinulata - Haldar, Saikat; Mulani, Fayaj A.; Aarthy, Thiagarayaselvam; Thulasiram, Hirekodathakallu V. (Journal of Organic Chemistry, 2015)
Regio- and stereoselective 11 beta-hydroxylation was achieved on the basic limonoid skeleton through microbial transformation. Whole cells of Cunninghamella echinulata efficiently converted basic limonoids such as epoxyazadiradione, azadiradione, and gedunin to their 11 beta-hydroxy analogues as the sole metabolite. Fermentation conditions affecting the efficiency (96%) of biotransformation including substrate concentration, incubation period, pH, and temperature were optimized. The position and stereochemistry of hydroxyl functionality on the isolated metabolites were established through extensive spectroscopic and spectrometric studies (1D, 2D NMR, ESI-MS, and MS/MS).

Azadirachta indica triterpenoids promote osteoblast differentiation and mineralization in vitro and in vivo - Kushwaha, Priyanka; Khedgikar, Vikram; Haldar, Saikat; Gautam, Jyoti; Mulani, Fayaj A.; Thulasiram, Hirekodathakallu V.; Trivedi, Ritu (Bioorganic & Medicinal Chemistry Letters, 2016)
Terpenoids were isolated using chromatographic purification through solvent purification technique and identified as Azadirone (1), Epoxyazadiradione (2) Azadiradione (3) Gedunin (4) Nimbin (5) Salannin (6) Azadirachtin A (7) and Azadirachtin B (8) from Azadirachta indica. Out of eight compounds, only three compounds had osteogenic activity and enhanced osteoblast proliferation, differentiation and mineralization in osteoblast cells. Active compounds stimulated osteogenic genes ALP, RunX-2 and OCN expressions in vitro, but Azadirachtin A had a maximum ability to stimulate osteoblast differentiation and mineralization compared to other two active compounds. For in vivo study, Azadirachtin A injected subcutaneously in pups, which enhanced osteogenic gene expressions and promoted bone formation rate significantly. Here, we conclude that active compounds of Azadirachta indica have osteogenic activity and Azadirachtin A has a beneficial effects on bone. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: ALP and mineralization assay; Balb/c mice pups; Calvarial osteoblast cells; Gene expressions

Comparative functional characterization of eugenol synthase from four different ocimum species: implications on eugenol accumulation - Anand, Atul; Jayaramaiah, Ramesha H.; Beedkar, Supriya D.; Singh, Priyanka A.; Joshi, Rakesh S.; Mulani, Fayaj A.; Dholakia, Bhushan B.; Punekar, Sachin A.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2016)
Isoprenoids and phenylpropanoids are the major secondary metabolite constituents in Ocimum genus. Though enzymes from phenylpropanoid pathway have been characterized from few plants, limited information exists on how they modulate levels of secondary metabolites. Here, we performed phenylpropanoid profiling in different tissues from five Ocimum species, which revealed significant variations in secondary metabolites including eugenol, eugenol methyl ether, estragole and methyl cinnamate levels. Expression analysis of eugenol synthase (EGS) gene showed higher transcript levels especially in young leaves and inflorescence; and were positively correlated with eugenol contents. Additionally, transcript levels of coniferyl alcohol acyl transferase, a key enzyme diverting pool of substrate to phenylpropanoids, were in accordance with their abundance in respective species. In particular, eugenol methyl transferase expression positively correlated with higher levels of eugenol methyl ether in Ocimum tenuiflorum. Further, EGSs were functionally characterized from four Ocimum species varying in their eugenol contents. Kinetic and expression analyses indicated, higher enzyme turnover and transcripts levels, in species accumulating more eugenol. Moreover, biochemical and bioinformatics studies demonstrated that coniferyl acetate was the preferred substrate over coumaryl acetate when used, individually or together, in the enzyme assay. Overall, this study revealed the preliminary evidence for varied accumulation of eugenol and its abundance over chavicol in these Ocimum species. Current findings could potentially provide novel insights for metabolic modulations in medicinal and aromatic plants. (C) 2016 Elsevier B.V. All rights reserved.

Epoxyazadiradione suppresses breast tumor growth through mitochondrial depolarization and caspase-dependent apoptosis by targeting PI3K/Akt pathway - Kumar, Dhiraj; Haldar, Saikat; Gorain, Mahadeo; Kumar, Santosh; Mulani, Fayaj A.; Yadav, Amit S.; Miele, Lucio; Thulasiram, Hirekodathakallu V.; Kundu, Gopal C. (BMC Cancer, 2018)
Background: Breast cancer is one of the most commonly diagnosed invasive cancers among women around the world. Among several subtypes, triple negative breast cancer (TNBC) is highly aggressive and chemoresistant. Treatment of TNBC patients has been challenging due to heterogeneity and devoid of well-defined molecular targets. Thus, identification of novel effective and selective agents against TNBC is essential. Methods: We used epoxyazadiradione to assess the cell viability, mitochondrial potential, ROS level, cell migration, apoptosis and protein expression in cell culture models of TNBC MDA-MB-231 and ER+MCF-7 breast cancer cells. The molecular mechanism was examined in two different type of breast cancer cells in response to epoxyazadiradione. We have also analyzed the effect of epoxyazadiradione on breast tumor growth using in vivo mice model. Results: In this study, we for the first time investigated that out of 10 major limonoids isolated from Azadirachta indica, epoxyazadiradione exhibits most potent anti-cancer activity in both TNBC and ER+breast cancer cells. Epoxyazadiradione induces apoptosis and inhibits PI3K/Akt-mediated mitochondrial potential, cell viability, migration and angiogenesis. It also inhibits the expression of pro-angiogenic and pro-metastatic genes such as Cox2, OPN, VEGF and MMP-9 in these cells. Furthermore, epoxyazadiradione attenuates PI3K/Akt- mediated AP-1 activation. Our in vivo data revealed that epoxyazadiradione suppresses breast tumor growth and angiogenesis in orthotopic NOD/SCID mice model. Conclusion: Our findings demonstrate that epoxyazadiradione inhibits PI3K/Akt-dependent mitochondrial depolarisation, induces apoptosis and attenuates cell migration, angiogenesis and breast tumor growth suggesting that this compound may act as a potent therapeutic agent for the management of breast cancer.
Keywords: Angiogenesis; Apoptosis; Breast cancer; Limonoids; Metastasis; PI3K

Regioselective and efficient enzymatic synthesis of antimicrobial andrographolide derivatives - Patil, Harshal S.; Jadhav, Dipesh D.; Paul, Ajay; Mulani, Fayaj A.; Karegaonkar, Shrikant J.; Thulasiram, Hirekodathakallu V. (Bioorganic & Medicinal Chemistry Letters, 2018)
Labdane diterpene andrographolide (1) is a major constituent of Andrographis paniculata and known to exhibit wide spectrum of biological activities. In this study, regioselective monoesters of (1) have been synthesized by using Amano lipase AK (Pseudomonas fluorescens) as a biocatalyst. Amano lipase AK was able to execute highly efficient esterification of hydroxyl group attached to C-14 carbon of (1) in presence of acyl donors. Among the various synthesized derivatives including two novel compounds such as andrographolide-14-propionate (3) and andrographolide-14-caproate (5) displayed antimicrobial activity against Staphylococcus aureus with low minimal inhibitory concentration (MIC) 4 mu g/mL and 16 mu g/mL respectively. Furthermore, they have shown low hemolysis activity at their respective MIC and increase in the permeability of the bacterial cell membrane as delineated by FITC uptake and SEM imaging studies. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Acylation; Andrographolide; Antimicrobial activity; biocatalysis; Hemolysis; Lipase; Natural product

Tracing the biosynthetic origin of limonoids and their functional groups through stable isotope labeling and inhibition in neem tree (Azadirachta indica) cell suspension - Aarthy, Thiagarayaselvam; Mulani, Fayaj A.; Pandreka, Avinash; Kumar, Ashish; Nandikol, Sharvani S.; Haldar, Saikat; Thulasiram, Hirekodathakallu V. (BMC Plant Biology, 2018)
Background Neem tree serves as a cornucopia for triterpenoids called limonoids that are of profound interest to humans due to their diverse biological activities. However, the biosynthetic pathway that plant employs for the production of limonoids remains unexplored for this wonder tree. Results Herein, we report the tracing of limonoid biosynthetic pathway through feeding experiments using C-13 isotopologues of glucose in neem cell suspension. Growth and development specific limonoid spectrum of neem seedling and time dependent limonoid biosynthetic characteristics of cell lines were established. Further to understand the role of mevalonic acid (MVA) and methylerythritol phosphate (MEP) pathways in limonoid biosynthesis, Ultra Performance Liquid Chromatography (UPLC)- tandem mass spectrometry based structure-fragment relationship developed for limonoids and their isotopologues have been utilized. Analyses of labeled limonoid extract lead to the identification of signature isoprenoid units involved in azadirachtin and other limonoid biosynthesis, which are found to be formed through mevalonate pathway. This was further confirmed by treatment of cell suspension with mevinolin, a specific inhibitor for MVA pathway, which resulted in drastic decrease in limonoid levels whereas their biosynthesis was unaffected with fosmidomycin mediated plastidial methylerythritol 4-phosphate (MEP) pathway inhibition. This was also conspicuous, as the expression level of genes encoding for the rate-limiting enzyme of MVA pathway, 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMGR) was comparatively higher to that of deoxyxylulose-phosphate synthase (DXS) of MEP pathway in different tissues and also in the in vitro grown cells. Thus, this study will give a comprehensive understanding of limonoid biosynthetic pathway with differential contribution of MVA and MEP pathways. Conclusions Limonoid biosynthesis of neem tree and cell lines have been unraveled through comparative quantification of limonoids with that of neem tree and through C-13 limonoid isotopologues analysis. The undifferentiated cell lines of neem suspension produced a spectrum of C-seco limonoids, similar to parental tissue, kernel. Azadirachtin, a C-seco limonoid is produced in young tender leaves of plant whereas in the hard mature leaves of tree, ring intact limonoid nimocinol accumulates in high level. Furthermore, mevalonate pathway exclusively contributes for isoprene units of limonoids as evidenced through stable isotope labeling and no complementation of MEP pathway was observed with mevalonate pathway dysfunction, using chemical inhibitors.

Estrogen receptor activation in response to Azadirachtin A stimulates osteoblast differentiation and bone formation in mice - Kushwaha, Priyanka; Ahmad, Naseer; Dhar, V. Yogeshwar; Verma, Ashwni; Haldar, Saikat; Mulani, Fayaj A.; Trivedi, Prabodh K.; Mishra, Prabhat R.; Thulasiram, V. Hirekodathakallu; Trivedi, Ritu (Journal of Cellular Physiology, 2019)
The positive effectsof the sex hormone in sustaining bone homeostasis areexercised by maintaining the equilibrium betweencell activity and apoptosis. In this regard, the importance of estrogen receptors in maintaining the bone is that it is anattractive drug target,if devoid of known side effects. In this study, we show that a natural pure compound Azadirachtin A (Aza A) isolated from Azadirachta indica binds selectively to a site in the estrogen receptor, identifying itself to bea selective tissue modifier. Using computational and medicinal chemistry, we show that Aza A binds potentially and selectively to estrogen receptor-alpha (ER alpha) as compared with ER beta. This preferential binding of Aza A to ER alpha with good pharmacokinetic distribution in the body forms metabolites, showing that it is well absorbed. In in vivo estrogen deficiency models for osteoporosis, Aza A at a much lower dose enhances new bone formation at both sites of the trabecular and cortical bone with increased bone strength and presentswith no hyperplastic effect in the uterus.
Keywords: ALP; Gene expression; micro-CT; mineralization; osteoblast cells

Basic limonoid modulates chaperone-mediated proteostasis and dissolve Tau fibrils - Gorantla, Nalini Vijay; Das, Rashmi; Chidambaram, Hariharakrishnan; Dubey, Tushar; Mulani, Fayaj A.; Thulasiram, V. Hirekodathakallu; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
The Alzheimer's disease pathology is associated with accumulation of intracellular neurofibrillary tangles and extracellular senile plaques. The formation of initial nucleus triggers conformational changes in Tau and leads to its deposition. Hence, there is a need to eliminate these toxic proteins for proper functioning of neuronal cells. In this aspect, we screened the effect of basic limonoids such as gedunin, epoxyazadiradione, azadirone and azadiradione on inhibiting Tau aggregation as well as disintegration of induced Tau aggregates. It was observed that these basic limonoids effectively prevented aggregates formation by Tau and also exhibited the property of destabilizing matured Tau aggregates. The molecular docking analysis suggests that the basic limonoids interact with hexapeptide regions of aggregated Tau. Although these limonoids caused the conformational changes in Tau to beta-sheet structure, the cytological studies indicate that basic limonoids rescued cell death. The dual role of limonoids in Tau aggregation inhibition and disintegration of matured aggregates suggests them to be potent molecules in overcoming Tau pathology. Further, their origin from a medicinally important plant neem, which known to possess remarkable biological activities was also found to play protective role in HEK293T cells. Basic limonoids were non-toxic to HEK293T cells and also aided in activation of HSF1 by inducing its accumulation in nucleus. Western blotting and immunofluorescence studies showed that HSF1 in downstream increased the transcription of Hsp70 thus, aggravating cytosolic Hsp70 levels that can channel clearance of aberrant Tau. All these results mark basic limonoids as potential therapeutic natural products.

Accurate identification of bioactive meliaceae limonoids by UHPLC-MS/ms based structure-fragment relationships (SFRs) - Mulani, Fayaj A.; Nandikol, Sharvani S.; Haldar, Saikat; Thulasiram, V, Hirekodathakallu (ACS Omega, 2021)
Y Limonoids are bioactive plant specialized metabolites found in the Meliaceae family. The basic limonoids, i.e., azadiradione, epoxyazadiradione, and gedunin have been exploited for various bioactivities and therefore are the potential drug leads for tomorrow. However, their low abundance, structural similarity, and lack of adequate mass fragmentation data have hampered their accurate identification and quantification from various sources. In the present study, basic limonoids such as azadirone, azadiradione, epoxyazadiradione, and gedunin isolated from Neem were utilized for the synthesis of their derivatives and isotopologs. A total of 30 one compounds were used in this study among which five were isolated, two were biotransformed, and 24 were synthesized. Among the synthesized compounds nine are novel compounds including six deuterated analogs/isotopologs which are (1,3-H-2)-1,2dihydro-3 beta-hydroxyazadiradione (9), (1,3,16-H-2)-1,2-dihydro-3 beta-16 beta-dihydroxyazadiradione (10), 3 beta-hydroxyazadiradione (11), 3 beta-16 beta-dihydroxyazadiradione (12), (3-H-2)-3 beta-hydroxyazadiradione (13), (3,16-H-2)-3 beta-16 beta-dihydroxyazadiradione (14), (1,3,7-H-2)-1,2-dihydro-3 beta-hydroxy-7-deacetylazadiradione (15), 1,2,20,21,22,23-hexahydroazadiradione (17), and (1,3-H-2)-1,2-dihydro-3 beta-hydroxygedunin (29). These limonoids along with their semisynthesized derivatives were subjected to ultra high performance liquid chromatography mass spectrometry (UHPLC-MS/MS) and the fragmentation pathway was established based on structure-fragment relationships (SFRs), utilizing high resolution MS/MS data. We have developed a most reliable and easily reproducible protocol describing in depth analysis of SFRs based on the structural modifications and synthesis of isotopologs. Also, the MS/MS fragment library of these basic limonoids generated in this study acts as a fingerprint for accurate identification and quantification of limonoids by MS/MS analysis in various plant tissue extracts, phytopharmaceutical formulations and biological samples.

Limonoid biosynthesis 3: functional characterization of crucial genes involved in neem limonoid biosynthesis - Pandreka, Avinash; Chaya, Patil S.; Kumar, Ashish; Aarthy, Thiagarayaselvam; Mulani, Fayaj A.; Bhagyashree, Date D.; Shilpashree, H. B.; Jennifer, Cheruvathur; Ponnusamy, Sudha; Nagegowda, Dinesh; Thulasiram, V. Hirekodathakallu (Phytochemistry, 2021)
Neem (Azadirachta indica L.) is well known for its medicinal, agricultural, and pesticidal applications since ages. The secondary metabolites, limonoids, confer these biological properties, wherein over 150 different limonoids have been reported from neem. To understand limonoid biosynthesis, we analyzed tissue-specific (kernel, pericarp, leaves, and flower) transcriptome that resulted in the identification of one farnesyl diphosphate synthase (AiFDS), one squalene synthase (AiSQS), three squalene epoxidases (AiSQE1, AiSQE2, and AiSQE3), two triterpene synthases (AiTTS1 and AiTTS2), cycloartenol synthase (AiCAS), two cytochrome P450 reductases, and ten cytochrome P450 systems. Comparative tissue-expression analysis indicated that AiFDS, AiSQS, AiSQE3, and AiTTS1 are expressed higher in the kernel than in the other tissues. Heterologously expressed recombinant AiTTS1 produced tirucalla-7,24-dien-3 beta-ol as the sole product. Expression profile data, phylogeny with triterpene synthases from Meliaceae and Rutaceae families, real-time PCR of different tissues, and transient transformation revealed the involvement of tirucalla-7,24-dien-3 beta-ol synthase (AiTTS1) in limonoid biosynthesis. Further, mutagenesis studies of AiTTS1 indicated that Y125 and F260 are probably involved in stabilization of dammarenyl cation. A 2.6-fold increase in production of tirucalla-7,24-dien-3 beta-ol was observed when AiSQE1 was coexpressed with mutant AiTTS1 in a yeast system. Furthermore, we functionally characterized the highly expressed cytochrome P450 reductases and cycloartenol synthase. This study helps in further analysis and identification of genes involved in limonoid biosynthesis in Meliaceae/Rutaceae and their production in a metabolically tractable heterologous system.
Keywords: 24-dien-3 beta-ol; Azadirachta indica A. Juss.; Cytochrome P450 system; Limonoids; Meliaceae; Tirucalla-7; Transcriptome

Limonoid biosynthesis 3: functional characterization of crucial genes involved in neem limonoid biosynthesis (vol 184, 112669, 2021) - Pandreka, Avinash; Chaya, Patil S.; Kumar, Ashish; Aarthy, Thiagarayaselvam; Mulani, Fayaj A.; Bhagyashree, Date D.; Shilpashree, H. B.; Jennifer, Cheruvathur; Ponnusamy, Sudha; Nagegowda, Dinesh; Thulasiram, Hirekodathakallu V. (Phytochemistry, 2021)

Diversity assessment of Gloriosa superba accessions from Western Ghats of India based on morphological traits, ISSR markers and metabolite content - Mahajan, Yogesh A.; Shinde, Balkrishna A.; Mulani, Fayaj A.; Gade, Akshay B.; Kasodekar, Amol K.; Thulasiram, H. V.; Kadoo, Narendra Y.; Nikam, Tukaram D. (Journal of Applied Research on Medicinal and Aromatic Plants, 2022)
Gloriosa superba L. (glory lily) is a medicinally and horticulturally important plant used as a commercial source of the alkaloid colchicine. The Western Ghats in India is mostly unexplored for the morphological, genetic, and metabolite diversity of the species. In the current study, three methodologies were employed to assess the diversity among 50 established accessions of G. superba collected from several locations in the Western Ghats. The morphological analysis revealed that, among the studied traits, seed yield per vine and dry seed weight per 100 seeds for the established accessions were the most diverse traits. The former exhibited a significantly positive correlation with four vegetative and five yield traits. The first three principal components showed nine traits contributing to the variation. Intra-specific molecular variation based on inter simple sequence repeat markers distributed the accessions in three clusters with high polymorphism and low genetic diversity indices. Liquid chromatography high-resolution mass spectrometry analysis revealed significant variation among the screened accessions for colchicine content in tuber and seed tissue. Interestingly, an unexplored tissue, pod shell, was found to contain significantly high colchicine, which could be explored for commercial colchicine extraction. The morphogenetic and metabolite variation revealed by the study would be useful to develop elite varieties to expand the cultivation of glory lily across the country, fulfilling the increasing demand for colchicine and providing remunerative income to the farmers.
Keywords: Colchicine; Genetic diversity; Gloriosa superba; Metabolite diversity; Morphological diversity; Western Ghats

Ultra-high performance liquid chromatography Q-Orbitrap MS/MS-based profiling and quantification of limonoids in Meliaceae plants - Mulani, Fayaj A.; Nandikol, Sharvani S.; Kajjihundi, Jagadeesh S.; Pathappa, Niranjana; Puttappa, Sharanappa; Thulasiram, V. Hirekodathakallu (Analytical and Bioanalytical Chemistry, 2022)
Meliaceae plants have been extensively used in agriculture, folklore, and traditional medicine. They are the major storehouses for structurally diverse limonoids (meliacins) possessing various bioactivities like antifeedant, insecticidal, antimicrobial, etc. However accurate detection of these tetranortriterpenes from the vast pool of metabolites in plant tissue extracts or biological sample is a crucial challenge. Though the mass spectrum (MS) provides the molecular mass and the corresponding elemental composition, it cannot be relied precisely. The exact identification of a specific metabolite demands the MS/MS spectrum containing the signature product ions. In the present study, we have developed the UHPLC Q-Orbitrap-based method for identification, quantification, and characterization of limonoids in different plant tissue extracts requiring minimum plant material. Using this method, we carried out the limonoid profiling in different tissue extracts of sixteen Meliaceae plants and the identification of limonoids was performed by comparing the retention time (RT), ESI-(+)-MS spectrum, and HCD-MS/MS of the purified fifteen limonoids used as reference standards. Our results revealed that early intermediates of the limonoid biosynthetic pathway such as azadiradione, epoxyazadiradione, and gedunin occurred more commonly in Meliaceae plants. The MS/MS spectrum library of the fifteen limonoids generated in this study can be utilized for identification of these limonoids in other plant tissue extracts, botanical fertilizers, agrochemical formulations, and bio pesticides.
Keywords: LC-HRMS; LC-MS/MS; Limonoids; Meliaceae; Natural product; Quantification